Investment portfolio optimization using evolutionary strategies - Zou, Menglin (2014)
A successful investment will be based on two factors, securities analysis and portfolio management. Researches showed that most markets are efficient markets, which means on a well-developed securities exchange, asset prices accurately reflect the trade-off between the relative risk and potential return associated with the security. Thus, the chance of picking an undervalued securities is relatively low and a properly constructed portfolio with optimal level of expected return and the least possible risk would be more desirable in the current context.